TANTANGAN YURIDIS DAN HARMONISASI REGULASI KEDUDUKAN AKTA NOTARIS DALAM PEMBUKTIAN PERJANJIAN ELEKTRONIK DI ERA DIGITAL INDONESIA - Zulfikar, Zulfikar; Meiliawati, Indri (Sekolah Tinggi Ilmu Hukum Graha Kirana, 2025)
AbstractThe advancement of digital technology has significantly transformed the nature and mechanisms of legal agreements, including the evidentiary function of electronic contracts. However, a regulatory discrepancy exists between the Indonesian Law on Notary Position (UUJN) and the Law on Electronic Information and Transactions (UU ITE), particularly concerning the legal status of notarial deeds in digital settings. The main issue lies in the absence of clear provisions that recognise and regulate the role of notaries in authenticating electronic agreements, thereby leading to legal uncertainty. This study aims to identify the juridical challenges and formulate an ideal model of regulatory harmonisation. A normative juridical method is employed, using statutory and comparative approaches. The findings indicate that the legal position of notarial deeds in electronic agreements remains unrecognised due to the lack of supporting norms for digitalised notarial practice. It is concluded that regulatory harmonisation is urgently required through the revision of UUJN, the strengthening of notarial roles under UU ITE, and the establishment of a national digital notarial system to ensure legal certainty in the era of digital transformation.AbstrakPerkembangan teknologi digital telah mengubah bentuk dan mekanisme perjanjian hukum, termasuk dalam pembuktian perjanjian elektronik. Namun, terdapat ketidakharmonisan antara Undang-Undang Jabatan Notaris (UUJN) dan Undang-Undang Informasi dan Transaksi Elektronik (UU ITE) terkait kedudukan akta notaris dalam konteks digital. Permasalahan utama terletak pada absennya pengaturan yang mengakomodasi peran notaris dalam otentikasi perjanjian elektronik, sehingga menimbulkan ketidakpastian hukum. Penelitian ini bertujuan untuk mengidentifikasi tantangan yuridis yang dihadapi serta merumuskan model harmonisasi regulasi yang ideal. Metode yang digunakan adalah yuridis normatif dengan pendekatan peraturan perundang-undangan dan studi komparatif. Hasil pembahasan menunjukkan bahwa kedudukan akta notaris dalam perjanjian elektronik belum terlindungi secara hukum akibat belum adanya norma yang mendukung digitalisasi kenotariatan. Kesimpulannya, diperlukan harmonisasi regulasi melalui revisi UUJN dan penguatan peran notaris dalam UU ITE, serta pembentukan sistem kenotariatan digital nasional untuk menjamin kepastian hukum di era transformasi digital.